Examination of Darkside of Entrepreneurship among Business Owners in Lagos Nigeria - Aladejebi, Olufemi; Bamkole, Peter; Amao-Taiwo, Bukola (Archives of Business Research, 2024)
Being an entrepreneur is often viewed as a glamorous and rewarding experience. But behind the scenes, it can be a lonely and stressful journey. With long hours, endless responsibilities, and high expectations, it's not surprising that many founders struggle with mental health issues like depression and anxiety. The study aims to investigate the Darkside of Entrepreneurship among Business Owners in Lagos, Nigeria. The Theoretical framework for the study is the Disappointment theory. The research method used in the study is a detailed survey, which was used to collect data from 412 business owners in Lagos whose businesses were five years and above, operating in different fields. Five Likert scale was used to collect data. It is with the purpose of understanding the causes that lie behind those aspects of entrepreneurship that are less desirable, including economic vulnerability, work overload and even symptoms of mental health disorders. Another significant aspect, which is evident from the investigation, is that individuals aspiring for self-employment are highly stressed with reference to income volatility and chances of business closure. Also, the findings revealed frequent physical-neurological stress factors affecting entrepreneurs. Even while the experts acknowledge many of the factors, such as strategic thinking, having a budget plan, and networking, several individuals indicate that those areas pose challenges in terms of infringing on their health and family. Interestingly, the study also elicits ambivalent attitudes about State aid and the advantages of being part of the chamber of commerce/trade associations. On the basis of these findings, it presents a number of imperative recommendations: increasing the funding and accessibility of financial support services, encouraging organisations to improve work-family balance, establishing an easily understandable framework for regulations and standards, and providing easy access to mental health support services. With these challenges addressed, there is potential to grow the entrepreneurial ecosystem in Lagos, which will benefit all parties interested in buying from local businesses.